FAKTOR-FAKTOR RISIKO KEJADIAN PREEKLAMPSIA PADA IBU HAMIL DI RSUD BANYUMAS TAHUN 2011 - Tin Utami (Universitas Harapan Bangsa Purwokerto, 2012)
Objective: The purpose of this research was to determine the risk factors forpreeclampsia in pregnant women in Banyumas General Hospital in 2011.Method: Methods This research is descriptive Retrospective Study. The samplewas pregnant with the number of 324 respondents drawn using purposivesampling technique.Results: The results of this research are risk factors for preeclampsia is largelydominated by age group> 35 years were 51 respondents (68%), paritygrandemultipara many as 13 respondents (65%), history of hypertension as muchas 109 respondents (66.5), and who experienced pregnancy double as much as 8respondents (80%).Conclusion: The conclusion of this research that factor - is a risk factor forpreeclampsia in pregnant women over the age of 35 years, paritygrandemultipara, had a history of hypertension and those with multiplepregnancy. Keywords: Risk Factors Preeclampsia, Pregnancy.